The Impact of Social Media Usage on Work Efficiency: The Perspectives of Media Synchronicity and Gratifications - Jong, Din; Chen, Shih-Chih; Ruangkanjanases, Athapol; Chang, Yun-Hsuan (Frontiers in Psychology, 2021)
As prevail of mobile networking, social media became ubiquitous in either work or our personal life. Based on Media Synchronization Theory and transformational framework, this study proposed a research model and examined how the social media’ attributes impacting the work effectiveness through the work-oriented or social-oriented usage. The data of 322 valid questionnaires from respondents was analyzed by SmartPLS 3.2.8. The results indicated that the features of social media including availability and symbol variety had the significant influences on their work efficiency through work-oriented usage of social media. Publicness and symbol variety had impact on work efficiency via social-oriented usage of social media. In addition, both social media for work-oriented and social-oriented usage influenced employees’ work efficiency. There were different considerations when people selected social media for work or for social purpose. Managers or companies could guide their employees to use the social media in a right way to increase their work features to complete their work efficiency, and create groups for employees so the work information could be shared efficiently.